2001
DOI: 10.1021/ma0101052
|View full text |Cite
|
Sign up to set email alerts
|

An Immobilized/Soluble Hybrid Catalyst System for Atom Transfer Radical Polymerization

Abstract: A new two-component catalyst system consisting of an immobilized catalyst and a soluble catalyst in ppm quantities was applied to atom transfer radical polymerization (ATRP). A high conversion of monomer (>90%) was achieved with a predetermined molecular weight and narrow molecular weight distribution (M w/Mn ) 1.1-1.3) in the ATRP of methyl methacrylate and methyl acrylate. The immobilized catalyst was removed by a filtration or sedimentation procedure. The casting of the reaction solution afforded clear and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
140
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(143 citation statements)
references
References 15 publications
2
140
1
Order By: Relevance
“…Special handling procedures are often required to remove all oxygen and oxidants from these systems. Previous research intending to streamline the process and products of ATRP has focused on maximizing the efficiency of catalyst removal or recycling through the use of ion-exchange resins (13), biphasic systems (14), immobilized͞solid-supported catalysts (12), and immobilized͞soluble hybrid catalyst systems (15). By contrast, the work presented hereafter demonstrates how several recently developed ATRP initiation systems can be implemented to both scavenge oxidants and decrease the amount of catalyst needed (to ppm levels) where its removal or recycling would be unwarranted for many industrial applications.…”
mentioning
confidence: 99%
“…Special handling procedures are often required to remove all oxygen and oxidants from these systems. Previous research intending to streamline the process and products of ATRP has focused on maximizing the efficiency of catalyst removal or recycling through the use of ion-exchange resins (13), biphasic systems (14), immobilized͞solid-supported catalysts (12), and immobilized͞soluble hybrid catalyst systems (15). By contrast, the work presented hereafter demonstrates how several recently developed ATRP initiation systems can be implemented to both scavenge oxidants and decrease the amount of catalyst needed (to ppm levels) where its removal or recycling would be unwarranted for many industrial applications.…”
mentioning
confidence: 99%
“…Again a decrease in activity, indicating loss of metal, was reported. A two-component catalyst system with a polymer-bound and a soluble Cu species was reported by Matyjaszewski and co-workers [138]. As might have been anticipated, the metal contents were in the range of 15-150 mg /kg.…”
Section: Cu-and Rh-based Systemsmentioning
confidence: 65%
“…In the recent literature [20 -22] there are also some examples of successful immobilization of catalysts that maintain their activity on a solid support. Matyjaszewski et al [23] reported a new two-component catalyst system consisting of an immobilized catalyst and a soluble catalyst in ppm quantities and applied this system in ATRP successfully. A high monomer conversion (>90%) was achieved with a predetermined molecular weight and narrow molecular weight distribution (M w /M n 1.1-1.3) in the ATRP of MMA and MA.…”
Section: Introductionmentioning
confidence: 99%